Decentralising voice: women’s participation in Integrated Development Planning processes in KwaZulu-Natal, South Africa. - Williamson, Amanda; Sithole, Pearl; Todes, Alison (Paper presented to Conference on the Place of Participation in a democratising South Africa, IFAS, HSRC and CUBES, Wits, 20-21st November, 2006., 2006)
The appeal of decentralisation is based on the belief that it will foster participatory democracy, introduce more responsive service delivery and advance the rights of citizens. It is also assumed that decentralisation processes will promote gender equity and benefit women. International experience, however, has begun to show that social transformation does not necessarily follow decentralisation processes, and that the increased autonomy enjoyed by local government can roll back advances secured by national government as local elites entrench their power in ways that exclude and disempower marginalised and vulnerable groups. Against a backdrop of ambivalent evidence feminist scholars have cautioned against an uncritical acceptance of the supposed benefits of decentralisation for women.
Keywords: Participatory democracy, integrated development planning, women participation